Dinamika Perilaku Orangutan Kalimantan (Pongo pygmaeus wurmbii) di Taman Nasional Sebangau Kalimantan Tengah: Behavior Dynamics of the Bornean Orangutan (Pongo pygmaeus wurmbii) in Sebangau National Park, Central Kalimantan - Panda, Adventus; Chandra Kasih, Rosenda (Jurnal Jejaring Matematika dan Sains, 2020)
Sebangau National Park represents a relatively intact peatland ecosystem and is one of the pockets of the P.p. ssp. wurmbii crucial in the world. Anthropological studies state that Orangutans have a social unit in a complex structure. The logical consequence of this condition is that many observed behaviors attract and open up new knowledge related to space use patterns. This study aims to uncover the dynamics of orangutan behavior by presenting critical evidence. This research is a descriptive exploratory study, using a non-invasive observation method with a camera trap approach, in the Punggualas area, from January 2012 to January 2014. The results show confirmation of walking on the forest floor as a new part of the orangutan association of behavior. Based on this, the conclusion drawn is that the dynamics of orangutan behavior develop dynamically in response to changes in natural habitat conditions.